2017
DOI: 10.1371/journal.pone.0175278
|View full text |Cite
|
Sign up to set email alerts
|

Sustained elevated levels of C-reactive protein and ferritin in pulmonary tuberculosis patients remaining culture positive upon treatment initiation

Abstract: BackgroundClinical trials that evaluate new anti-tubercular drugs and treatment regimens take years to complete due to the slow clearance of Mycobacterium tuberculosis infection and the lack of early biomarkers that predict treatment outcomes. Host Inflammation markers have been associated with tuberculosis (TB) pathogenesis. In the present study, we tested if circulating levels of C-reactive protein (CRP) and ferritin reflect mycobacterial loads and inflammation in pulmonary TB (PTB) patients undergoing anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 22 publications
4
36
3
Order By: Relevance
“…Previously published data also indicate that circulating CRP levels were significantly increased in active TB disease compared with controls . During M. tuberculosis infection, CRP levels are increased in TB patients starting ATT and decreased during the first 2 months of treatment, and these elevated CRP levels reflected higher AFB smear grades and correlated with disease severity . Similar to earlier findings, our data recapitulate those results and show that CRP levels are present at significantly enhanced levels in TB‐DM and TB compared with the other groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previously published data also indicate that circulating CRP levels were significantly increased in active TB disease compared with controls . During M. tuberculosis infection, CRP levels are increased in TB patients starting ATT and decreased during the first 2 months of treatment, and these elevated CRP levels reflected higher AFB smear grades and correlated with disease severity . Similar to earlier findings, our data recapitulate those results and show that CRP levels are present at significantly enhanced levels in TB‐DM and TB compared with the other groups.…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that pulmonary TB displayed heightened serum CRP levels compared with latent TB and extrapulmonary TB . Previously published data also indicate that circulating CRP levels were significantly increased in active TB disease compared with controls . During M. tuberculosis infection, CRP levels are increased in TB patients starting ATT and decreased during the first 2 months of treatment, and these elevated CRP levels reflected higher AFB smear grades and correlated with disease severity .…”
Section: Discussionmentioning
confidence: 81%
“…Second, ferritin levels are very high during severe graft-versus-host disease and during macrophage activation syndromes after alloSCT (12). Third, ferritin is an acute phase protein that is regularly elevated during acute and chronic infections (24,25). Ferritin has been implicated in fungal growth and high ferritin levels have previously been suggested to be a risk factor for infections after alloSCT (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Although promising, further research is needed to establish the efficacy of this new assay as marker for treatment monitoring and/or outcome. 166,195,196] [158] [172,173,197] [ 162,175] Markers of lung tissue repair (platelet activity VEGF, TGF-β, MMPs) [195,196] [135].…”
Section: T-cell Responsesmentioning
confidence: 99%
“…Circulating levels of C-reactive protein (CRP), an established biomarker of systemic inflammation, has been described to reflect TB disease severity and radiographic improvement after 2 months of treatment [162,163]. In an African study, CRP decreased significantly after 2 months of treatment, whereas levels of β 2 -microglobulin, a component of class I MHC found in a free state in various body fluids in different disease pathologies [164], and neopterin, a clinical marker of immune activation during inflammation [165] showed little change by 2 months, but a significant decrease after 6 months of treatment [166].…”
Section: Modulation Of Monocytic and Lymphocytic Cell Populationsmentioning
confidence: 99%